2016
DOI: 10.1186/s12879-016-1978-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative epidemiology of influenza A and B viral infection in a subtropical region: a 7-year surveillance in Okinawa, Japan

Abstract: BackgroundThe epidemic patterns of influenza B infection and their association with climate conditions are not well understood. Influenza surveillance in Okinawa is important for clarifying transmission patterns in both temperate and tropical regions. Using surveillance data, collected over 7 years in the subtropical region of Japan, this study aims to characterize the epidemic patterns of influenza B infection and its association with ambient temperature and relative humidity, in a parallel comparison with in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 36 publications
2
28
0
3
Order By: Relevance
“…Generally, influenza peak once in the winter in temperate areas (Finkelman et al, 2007), however, it seems that the seasonal patterns in tropical and subtropical zones are more complicated. Several previous studies reported that the peaking of seasonal influenza occurred once a year (in winter or spring/summer) in some subtropical areas (Cheng et al, 2012), however, other studies found the peaks in subtropical regions were detected in both summer and winter (Iha et al, 2016;Liu et al, 2017). Furthermore, the transmission patterns of seasonal influenza were very diverse in China by region (Du et al, 2012;Shu et al, 2010;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Generally, influenza peak once in the winter in temperate areas (Finkelman et al, 2007), however, it seems that the seasonal patterns in tropical and subtropical zones are more complicated. Several previous studies reported that the peaking of seasonal influenza occurred once a year (in winter or spring/summer) in some subtropical areas (Cheng et al, 2012), however, other studies found the peaks in subtropical regions were detected in both summer and winter (Iha et al, 2016;Liu et al, 2017). Furthermore, the transmission patterns of seasonal influenza were very diverse in China by region (Du et al, 2012;Shu et al, 2010;Yu et al, 2013).…”
Section: Introductionmentioning
confidence: 94%
“…Prior studies have reported that the epidemiology (e.g., seasonality) of influenza A and influenza B may differ from each other [8][9][10], and the relative importance of influenza A and influenza B in driving seasonal influenza peak may vary across different countries [11]. For the development of strategic seasonal influenza control programs (e.g., using trivalent vaccines or quadrivalent vaccines), it is essential to assess the proportions of influenza A virus and influenza B virus in seasonal influenza virus.…”
Section: Introductionmentioning
confidence: 99%
“…The most common cause of annual 51 million visits to physicians is respiratory viral disease. Two-thirds to three-quarters of acute respiratory disease are caused by viruses, belonging to different families [ (8,9). Acute viral respiratory diseases (influenza A, B, and adenovirus) are among the most common human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…During the previous century, influenza virus caused millions of deaths around the world [11,12(10, 11). Antigenic shifts in Influenza A and B viruses are sometimes observed in epidemics [ (9,12). Since adenoviruses have the ability to create various diseases in humans, including respiratory illnesses, availability of quick methods for diagnosis of these viruses is very important.…”
Section: Introductionmentioning
confidence: 99%